The body fat in children and young people with hearing dysfunctions from eastern Poland - Dąbrowski, Dominik; Bergier, Józef (Polish Journal of Public Health, 2010)
Introduction. Reviewing the research literature in the sciences of physical culture on the broadly understood development of people with physical disabilities, we usually find studies on the development of people with mental handicap with particular emphasis on light and moderate degree of disability. It therefore seemed justified to carry out research in the field of disability associated with impaired hearing, on which few research papers have been  focused  so far. When examining the issues of people with impaired hearing, it appears that disability is not visible for the first time since a disabled person is not different from others. The question then arises whether these persons differ in the baseline measurements of biological development.Aim. The aim of the research is to estimate the body fat distribution in people with hearing dysfunctions in eastern Poland. While looking for differences in body fat, the analysis results concerned the standards of healthy people living in eastern Poland.Material and methods. The paper presents only a part of an analysis that was carried out in 2004-2006 and it was related to the estimation of physical development and motor abilities. The study concerned 339 people aged 8-18 living in eastern Poland. Because of the extensive research on the problem of physical development attention was drawn only to the level of adipose tissue thereby ignoring other physical parameters of individual development. The study was of diagnostic character, and the research method was a survey in which the observation technique was used whereas the physical development diagnosis was done on the basis of anthropometric measurements.Results. The research shows that girls with hearing dysfunction are characterized by a lower level of fatness in comparison to healthy peers. In the case of boys, a similar relationship can be noticed but only in the early stage of life, later on the results were opposite – the body fat was higher.